The Bumble Bees of Florida, Bombus spp. - Lionel A. Stange (EDIS)
Bumble bees are easily recognized by the corbicula (pollen basket) on the hind tibiae in the females. They are beneficial insects that pollinate many native and ornamental plants. They can sting severely, so problem nests near human dwellings should be removed by experienced pest control operators. This revised 5-page fact sheet includes a key to the bumble bees in Florida. Written by Lionel A. Stange and published by the UF Department of Entomology and Nematology, December 2011.